Casein Hydrolysate and Casein–Iron Chelate as Natural Bioactive Compounds for Yoghurt Fortification - Anna Mandecka; Anna Dąbrowska; Łukasz Bobak; Marek Szołtysik (Applied Sciences, 2022)
The aim of the study was to apply the bioactive components casein hydrolysate and casein–iron chelate to yoghurt and to analyze their influence on product parameters. Casein was hydrolyzed with the non-commercial protease obtained from Yarrowia lipolytica yeast and subjected to chelating process with Fe2+ ions. Both preparations were introduced to yoghurt production as additives for elevation of dry matter by 2%. The control yoghurt was produced with the addition of skim milk powder. In the prepared experimental yoghurts, the content of dry matter [DM], protein, fat, as well as iron contents were determined. The conducted studies showed that in all analyzed yogurts, DM content was at a similar level, while the protein content was significantly (p < 0.05) higher in the variant containing 2% casein–iron chelate. In yoghurts with the casein–iron chelate as a bioactive compound, the iron concentration was about 61.5–123 times higher than in yoghurt with the addition of skim milk powder. It was shown that during storage the addition of casein–iron chelate positively influenced the number of analyzed microbe groups.